Impact of Emotional Intelligence and Motivation on Job Satisfaction among “Mystery Shoppers” - M, Anand Shankar Raja (Ushus Journal of Business Management, 2021)
This research paper focuses on “Mystery Shopping”, making mystery shoppers the target respondents of this research study. While previous studies have taken into consideration the motivational aspect, this research extends the scope to consider EI and its mediation between motivation and job satisfaction. Simple percentage analysis has been used to analyse the demographic profile of the respondents as well as an Exploratory Factor Analysis (EFA) and corresponding CFA. The hypothesized eleven factors of CFA (4 factors for motivation, 5 factors for Emotional Intelligence and 2 factors for job satisfaction) model fits the sample data very well. The major rule of thumb RMSEA is .87, RMR is 0.30 and AGFI is .891 which has satisfied the CFA model fit criteria. It is found that job satisfaction is enhanced only through motivation directly rather than being mediated by EI. Thus the lacking aspects have to be considered by the mystery shoppers to enhance job satisfaction through a well-balanced emotional state.